2007
DOI: 10.1038/nature06180
|View full text |Cite
|
Sign up to set email alerts
|

Nature of the superconductor–insulator transition in disordered superconductors

Abstract: The interplay of superconductivity and disorder has intrigued scientists for several decades. Disorder is expected to enhance the electrical resistance of a system, whereas superconductivity is associated with a zero-resistance state. Although, superconductivity Superconductivity-the occurrence of the zero-resistance state-has been a central issue in solid-state physics for nearly a hundred years. About half a century after its discovery Bardeen, Cooper and Schreiffer 13 (BCS) explained its microscopic foundat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
372
1
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(395 citation statements)
references
References 33 publications
16
372
1
6
Order By: Relevance
“…We also note that the superconducting islands we found in the "normal" phase (which is really insulating) have also been observed in numerical studies of superconductor-insulator transition in disordered superconductors. 43 Our results are in qualitative agreement with previous studies 31,32 which suggested that the the FFLO state can survive as long as the electron scattering rate is comparable or smaller than the BCS gap. In our study we find the critical disorder strength W c ≈ 2.0; this corresponds to a scattering rate (within effective mass approximation) 1/τ c ≈ W 2 c /(24 t) ≈ 0.167 (we set = 1), which is indeed comparable the the BCS gap ∆ = 0.365.…”
Section: Discussionsupporting
confidence: 83%
“…We also note that the superconducting islands we found in the "normal" phase (which is really insulating) have also been observed in numerical studies of superconductor-insulator transition in disordered superconductors. 43 Our results are in qualitative agreement with previous studies 31,32 which suggested that the the FFLO state can survive as long as the electron scattering rate is comparable or smaller than the BCS gap. In our study we find the critical disorder strength W c ≈ 2.0; this corresponds to a scattering rate (within effective mass approximation) 1/τ c ≈ W 2 c /(24 t) ≈ 0.167 (we set = 1), which is indeed comparable the the BCS gap ∆ = 0.365.…”
Section: Discussionsupporting
confidence: 83%
“…The substrate granularity results in disordered superconducting films, where the localization of charge carriers by Coulomb interaction and the corresponding enhancement of quantum fluctuations of the phase of the superconductor order parameter induces the superconductor-insulator transition. 13 Lowering the baking and deposition temperature leads to a dramatic improvement of the surface quality and superconducting properties. Figure 1͑c͒ shows the AFM images of a 4.5 nm NbN film deposited at 350°C, after a ͑200°C for 12 h, 350°C for 30 min͒ baking sequence.…”
Section: Nanowire Superconducting Single-photon Detectors On Gaas Formentioning
confidence: 99%
“…Moreover, understanding superconductivity in thin films is expected to clarify the behavior of resistance in thin metallic films in general. Likewise, it has even been suggested that the superconductivity-disorder interplay in thin films is the key to understanding high-T c superconductivity [4]. Therefore, it is the goal of this paper to demonstrate a universal behavior for T c in thin films as a function of both d and R s .…”
mentioning
confidence: 99%
“…Because superconductivity relies on a collective electron behavior, the onset of superconductivity occurs when the number of participating electrons is just enough to be considered collective, i.e., at the nanoscale [2][3][4][5]. Thus, it is known that the superconductivity-disorder interplay varies in thin films and is effectively tuned with the film thickness (d) or with the disorder in the system, which is represented by sheet resistance of the film at the normal state (R s ) [6][7][8][9][10].…”
mentioning
confidence: 99%